The Relationship between Social Capital and Burnout in Energy Health Professionals: A Meta-Analysis - Adriani, Rita Benya; Sulistyowati, Dwi; Hapsari, Happy Indri; Adriana, Nadya Puspita (Indonesian Journal of Medicine, 2024)
Background: Social capital is referred to as public resources and capital that can be accessed through social relationships and social involvement of the community to work together to achieve common goals in various groups and organizations. Burnout Syndrome experienced by health workers is a situation when health workers show behavior such as giving unpleasant responses to patients, delaying work, getting easily angry when colleagues or patients ask simple questions, complaining of feeling tired and dizzy quickly and worse, not caring about work and surrounding conditions. This research aims to estimate the relationship between social capital and burnout in professional health workers. Subjects and Method: This research is a systematic review and meta-analysis research using the PRISMA diagram. Article searches were carried out based on the PICO Model eligibility criteria. P= Health workers; I= Social capital; C= Low social capital; O= Fatigue. The articles used come from 3 databases, namely: PubMed, Google Scholar, and ScienceDirect. With keywords including "social capital" AND "burnout" AND "health workers" AND "cross section study". Filtered articles that met the requirements were analyzed using the RevMan 5.3 application. Results: A total of 11 case-control observational research articles as a source for meta-analysis of the relationship between social capital and burnout in professional health workers. This research shows that health workers with low social capital have a risk of experiencing burnout 1.86 times compared to health workers with high social capital, and the results are statistically significant (aOR= 1.86; 95% CI= 1.09 to 3.17; p< 0.02). Heterogeneity of research data shows I2= 89% so that the data distribution is declared heterogeneous (random effect model). Conclusion: Meta-analysis of 11 cross-sectional studies concluded that social capital increases burnout in health workers. Keywords: Social capital, burnout, health workers.